Inquiry into firm owner’s risk preference and output disparity: evidence from the small-scale manufacturing firms in the Tigray region, Ethiopia - Samson Gebrerufael; Getachew Kebede; Daniel Hadera; Guush Weldegbrial; Selam Abraha (Cogent Economics & Finance)
Employing the Bauer model, this paper presents the factors of risk preferences of small-scale manufacturing firm owners in the Tigray region, Ethiopia. Once we identify the determinants of risk preferences, we investigate the role of risk preferences on firm output disparities utilizing the Penrose growth/output disparity/model. The study uses primary data based on random survey of the small-scale manufacturing firm owners in the zonal towns of the Tigray region. The multinomial logit and the multiple linear regression models are employed to identify the estimates of the factors of the risk preferences and the output disparity. The risk preference category of each sample firm owner was captured by employing the paper-format implicit association test (IAT) contextualized for this study. As a factor of risk preference, we find the soft budget constraint is a statistically significant variable only for the risk-averse and the risk-neutral owners. The factor of the risk preference (good perception of risk faced) is a statistically significant variable only for the risk-lover owners. Unlike the controversial negative relationship between firm owner’s higher risk propensity and firm-level performances presented by some authors, this paper presents the normally expected positive relationship between the higher risk propensity and the output level.